Carolyn Halpin-Healy on her experience as Co-Founder and Executive Director of Arts & Minds in conversation with Sara Torres - Torres, Sara; Halpin-Healy, Carolyn (Arte, Individuo y Sociedad, 2017)
Arts&Minds is a non-for-prfit organization and its goal is to improve well-being for people living with dementia and their cargivers through meaningful contact with art. They partner with the Studio Museum in Harlem, the New York Historical Sociaty, El Museo del Barrio and the Metropolitan Museum of Art.